Relendo o Parménides de Platão - Maria do Céu Fialho (Ideia, 2020)
This book presents a collection of selected essays from the papers presented to the international conference on Plato's Parmenides on the occasion of the 2nd Meeting of the Mediterranean Section of the International Plato Society (Coimbra, 14-16 June 2012). It opens with an introduction to the different approaches to this most challenging dialogue taken by the contributors of the volume. Samuel Scolnicov helpfully brings together the theoretical and ethical dimensions of the Parmenides. Luc Brisson, Néstor Cordero, Maurizio Migliori, Franco Trabattoni, Francesco Fronterotta, Mario Jorge Carvalho, J.D.Bares Partal, Beatriz Bossi, Francesca Pizzuti and Gabriele Cornelli present an in-depth analysis and commentary of the main topics of the first and second part of the dialogue from different points of view. The book also includes further clarification of interpretation problems and the reception of this dialogue in late Antiquity and Renaissance.